Child and Adolescent Socialization in the “Music-Making for All” Festival and Competition Project - Krasil’nikov, Igor (2020)
The article examines the socialization of children and adolescents in the process of participating in the innovative festival and competition project “Music-Making for All” involving concerts in which school students perform along with professional orchestras. The basis for achieving the desired result is provided by the author’s pedagogical technology of interactive music activity, which presents living through the music in the process of its creation or perception based on complementary interaction with an external sound source. A teacher survey is employed as a method of identifying the indicators of the formation of socialization and the factors affecting the socialization process. The survey reveals numerous factors determining the successful socialization of a modern person. Creating a festive mood at the concerts of the project stimulates students’ interest in creative activity. High-quality repertoire orients young artists towards spiritual values. Overcoming the difficulties of music activity contributes to their personal self-affirmation. Interaction with the instrumental ensemble becomes an effective means of creative expression of students. The communicative skills of the younger generation develop in the process of creative communication between students, professional musicians, and the public. The desire of children and adolescents to establish friendships and work in a team contributes to the formation of moral qualities. Children realize the value of labor, acquire personal qualities valuable for successful socialization, such as higher self-esteem and ethical and aesthetic personal growth, and overcome personal issues.